ChemInform Abstract: Supported Au—Cu Bimetallic Alloy Nanoparticles: An Aerobic Oxidation Catalyst with Regenerable Activity by Visible‐Light Irradiation. Issue 33 (25th July 2013) - Sugano, Yoshitsune; Shiraishi, Yasuhiro; Tsukamoto, Daijiro; Ichikawa, Satoshi; Tanaka, Shunsuke; Hirai, Takayuki
Abstract Visible‐light irradiation (<450 nm) of Au—Cu alloy nanoparticles supported on Degussa P25 TiO2 successfully promotes aerobic oxidation of 2‐propanol without significant catalyst deactivation.